PROGRESS OF FORENSIC ENTOMOLOGY RESEARCH IN INDIA FROM PAST TO PRESENT - AMIN, M. RAFIQUL; SINHA, SHUVRA KANTI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
Research on Forensic Entomology was started in 1889 in India. Several workers in India experimented on this line but the field has much more to develop. The aim of the present review is to describe different dimensions of research like Carrion Ecology Study, Forensic Entomotoxicology Study, Aquatic Forensic Entomology Study, Forensic Entomology research using morphological approach, Forensic Entomology research using molecular approach, forensically important flies on weather factors as well as seasonal variation.